Inconsistencies of CSR Regulations in the Law Limited Liability Company in Relation to Justice Values - Adi Sartono Kn; Abdul Halim Barkatullah; Djoni Sumardi Gozali; Noor Hafidah (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2024)
The discussion in this journal is built on the inconsistencies in the regulations regarding CSR in Article 74 of Law Number 40 of 2007 concerning Limited Liability Companies, namely: First, the implementation of CSR is mandatory for companies that carry out their business in the field and/or related to natural resources. Second, the CSR funding system is voluntary. The purpose of this research is to find answers to the implications arising from the main problems mentioned above, namely: First, what are the legal implications in relation to justice from the inconsistency of regulations regarding CSR? Second, what is the ideal concept of CSR regulation? The research method used in this research is: descriptive normative research with a legal approach, legal theory and doctrine, and legal comparison. Research Results and Discussion: First, the implications of inconsistencies in CSR regulations in the Limited Liability Company Law can have an impact on the law enforcement process not being optimal in terms of justice, benefit and legal certainty as well as giving rise to unclear norms in relation to the CSR funding system which results in injustice for the community as the beneficiary CSR. Second, a more ideal concept of CSR regulation is: according to John Rowls’ Theory of Justice, if CSR funding sources are calculated from a portion of the Company’s profits, and according to Aristotle’s theory of justice, then the CSR funding system should be calculated as a percentage of the Company’s profits based on the principle of proportional equality between retention rights for Companies and the rights of the community as recipients of CSR benefits.